Atmospheric Forcing Drives the Winter Sea Ice Thickness Asymmetry of Hudson Bay. Issue 2 (12th February 2020) - Kirillov, S.; Babb, D.; Dmitrenko, I.; Landy, J.; Lukovich, J.; Ehn, J.; Sydor, K.; Barber, D.; Stroeve, J.
Abstract: Recently, we highlighted the presence of a strong west‐east asymmetry in sea ice thickness across Hudson Bay that is driven by cyclonic circulation. Building on this work, we use satellite altimetry and a unique set of in situ observations of ice thickness from three moored upward looking sonars to examine the role of atmospherically driven ice dynamics in producing contrasting regional ice thickness patterns. Ultimately, north‐northwesterly winds coupled with numerous reversals during winter 2016/2017 led to thicker ice in southern Hudson Bay, while enhanced west‐northwesterly winds during winter 2017/2018 led to thicker ice in eastern Hudson Bay that delayed breakup and onset of the summer shipping season to coastal communities. Extending the analysis over the 40‐year satellite observation period, we find that these two different patterns of atmospheric forcing alter the timing of breakup by 30 days in eastern Hudson Bay and offer some skill in seasonal predictions of breakup. Plain Language Summary: The seasonal ice cover of Hudson Bay is characterized by a pronounced east‐west asymmetry in ice thickness that is created by the regional pattern of ice drift. However, this asymmetry varies from year to year. Using in situ and remotely sensed observations of ice thickness, we contrast the two winters of 2016/2017 and 2017/2018 and investigate the role of atmospheric forcing in creating this asymmetry by deforming and thickening the ice cover in certain regions of Hudson Bay. It was found that stronger westerly winds increase ice thickness in eastern Hudson Bay by up to 50 cm at the end of winter. This in turn delays the breakup of the ice cover in eastern Hudson Bay, allowing ice to persist longer into summer, delaying the start of the open water shipping season and the summer resupply to coastal communities. Key Points: In situ and satellite observations reveal different spatial patterns of sea ice thickness (SIT) in Hudson Bay between winter 2017 and 2018 Differences of up to 0.5 m in eastern and southern Hudson Bay SITs are attributed to variability in wind driven ice dynamics Enhanced NW winds in winter increase SIT in eastern Hudson Bay, delaying spring breakup by 3–4 weeks and delaying navigation in summer